2012
DOI: 10.1345/aph.1r037
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Versus Actual Sedation Practices in Adult Intensive Care Unit Patients Receiving Mechanical Ventilation

Abstract: These data suggest differences in perceived and actual sedation practice in the US, as well as underutilization of evidence-based interventions. Most notable was the limited use of sedation treatment algorithms, daily interruption of sedation, and monitoring for delirium. Individual sedation and delirium protocols should be evaluated and updated based on evidence-based recommendations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
51
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 43 publications
1
51
1
1
Order By: Relevance
“…Within the observational study, a small percentage of all patients (5% and 6%, respectively) received a scheduled or an as-needed antipsychotic medication during the study period; haloperidol was the most frequently prescribed antipsychotic overall, primarily because of its use on as as-needed basis (accounting for 89% of as-needed antipsychotic doses). 15 The current study is, to the authors' knowledge, the first prospective description of Canadian ICU practices regarding antipsychotic drug use and delirium screening in mechanically ventilated patients, where delirium rates have been reported to be as high as 40%-80%. 8 The strengths of this study included prospective data collection, large sample size, multicentre design, and multiprovince representation.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Within the observational study, a small percentage of all patients (5% and 6%, respectively) received a scheduled or an as-needed antipsychotic medication during the study period; haloperidol was the most frequently prescribed antipsychotic overall, primarily because of its use on as as-needed basis (accounting for 89% of as-needed antipsychotic doses). 15 The current study is, to the authors' knowledge, the first prospective description of Canadian ICU practices regarding antipsychotic drug use and delirium screening in mechanically ventilated patients, where delirium rates have been reported to be as high as 40%-80%. 8 The strengths of this study included prospective data collection, large sample size, multicentre design, and multiprovince representation.…”
Section: Discussionmentioning
confidence: 93%
“…[1][2][3][4][5][6] Professional society guidelines 7,8 recommend the routine use of screening tools specifically designed for detecting delirium in critically ill patients (e.g., the Confusion Assessment Method for the Intensive Care Unit [CAM-ICU] 9 and the Intensive Care Delirium Screening Checklist [ICDSC] 10 ). However, international surveys and observational studies have indicated that delirium screening tools are not widely incorporated into critical care practice, [11][12][13][14][15][16] which represents a missed opportunity to detect the syndrome. As such, delirium may go unrecognized.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite differences in sedation goals, this finding was consistent in all 4 studies I examined and has been incorporated into much of the literature in favor of sedation-interruption protocols. [26][27][28][29] Of note, the study 6 with the smallest sample size, and the only study that included analgosedation, most likely was underpowered to confirm this assertion.…”
Section: Discussionmentioning
confidence: 99%
“…Nursedirected protocolized sedation and daily interruption (DI) of sedation are common sedation minimization strategies endorsed by current practice guidelines [1][2][3][4][5]. Although both strategies have been shown to be safe, clinical uptake is variable, with approximately 60% of clinicians using sedation protocols and less than 40% using DI [6,7]. Previously reported perceived barriers to the use of a sedation protocol include lack of a clear physician directive for use, nursing disinclination, and situations where the ICU clinician would like more control of sedation than a protocol permits [8].…”
Section: Introductionmentioning
confidence: 99%